2008
DOI: 10.2147/ndt.s3237
|View full text |Cite
|
Sign up to set email alerts
|

Update on ropinirole in the treatment of Parkinson’s disease

Abstract: Ropinirole is a dopamine agonist, approved for use to treat symptoms of early and advanced Parkinson's disease, is now available in a 24-hour formulation in addition to the immediate release version. This review discusses the mode of action of ropinirole and compares the pharmacokinetics of both formulations. Pivotal studies leading to the approval of both preparations are reviewed in terms of effi cacy, dose range and side effects. Patient factors such as compliance are discussed in terms of the place for rop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…From the past several decades to the present time, the most preferred therapeutic strategy in PD is to raise the level of dopamine in NCP by an exogenous supply of its precursor levodopa (L-DOPA). , Besides, DA-receptor agonists (e.g., bromocriptine, ropinirole, pergolide, pramipexole, etc. ), ,, MAO-B inhibitors (e.g., selegiline and rasagiline), , and COMT inhibitors (e.g., entacapone and tolcapone) have the potential to keep a raised level of dopamine in the brain and hence are recommended as adjunctive to L-DOPA therapy. Preclinical and clinical studies provided evidence of immense therapeutic benefits of neurotrophins (BDNF and GDNF), , antioxidants (vitamin E, CoQ10, mitoQ), ,, anti-inflammatory drugs (dexamethasone, ibuprofen, celecoxib, minocycline), α-synuclein inhibitors (anti-α-synuclein ASO, shRNA, aptamer, NPT200-11), , and compounds targeting the lysosome–proteosome dysfunction (ambroxol, nilotinib, Hsp therapy, beclin, and parkin gene therapy) in exhibiting anti-PD effects.…”
Section: Present Day Anti-pd Therapeutic Considerations and Their Lim...mentioning
confidence: 99%
See 2 more Smart Citations
“…From the past several decades to the present time, the most preferred therapeutic strategy in PD is to raise the level of dopamine in NCP by an exogenous supply of its precursor levodopa (L-DOPA). , Besides, DA-receptor agonists (e.g., bromocriptine, ropinirole, pergolide, pramipexole, etc. ), ,, MAO-B inhibitors (e.g., selegiline and rasagiline), , and COMT inhibitors (e.g., entacapone and tolcapone) have the potential to keep a raised level of dopamine in the brain and hence are recommended as adjunctive to L-DOPA therapy. Preclinical and clinical studies provided evidence of immense therapeutic benefits of neurotrophins (BDNF and GDNF), , antioxidants (vitamin E, CoQ10, mitoQ), ,, anti-inflammatory drugs (dexamethasone, ibuprofen, celecoxib, minocycline), α-synuclein inhibitors (anti-α-synuclein ASO, shRNA, aptamer, NPT200-11), , and compounds targeting the lysosome–proteosome dysfunction (ambroxol, nilotinib, Hsp therapy, beclin, and parkin gene therapy) in exhibiting anti-PD effects.…”
Section: Present Day Anti-pd Therapeutic Considerations and Their Lim...mentioning
confidence: 99%
“…Nanovesicular technology has further been explored in delivering both the ergot-derived (bromocriptine, pergolide, carbegoline, and lisuride) and non-ergoline (pramipexole, ropinirole, and apomorphine) dopamine receptor agonists. ,, This carrier-aided delivery has been adopted to counter the low BBB permeability and bioavailability of the agonists and reduce the occurrence of their allied side effects. , Administration of bromocriptine-encapsulated niosomes in PD rats resulted in prolonged drug release, remarkable bioavailability of the drug in the brain, reduced oxidative stress, and enhanced motor functions of the animals in comparison to free bromocriptine administration . The study further demonstrated that niosome administration did not lead to any toxicity or histopathology in the treated animals.…”
Section: Advances Made In Pd Treatment Strategies With the Assistance...mentioning
confidence: 99%
See 1 more Smart Citation
“…Levodopa rapidly gets metabolized, and the combination of levodopa along with some adjunct drugs such as carbidopa and entacapone is used to prevent its rapid metabolism in the plasma. However, the longstanding combination treatment of levodopa and carbidopa also causes several side effects. , For this purpose, ropinirole, bromocriptine, pergolide, cabergoline, and pramipexole (PPX) are used as a first-line treatment with or without levodopa to prevent the symptoms of PD. , …”
Section: Introductionmentioning
confidence: 99%
“…Dopamine levels, polymorphisms in dopamine receptor and transporter genes, and differential methylation of dopamineassociated genes are related to novelty-seeking and exploratory behavior in mammals and birds (Schinka et al, 2002;Fidler et al, 2007;Egan et al, 2009;Filby et al, 2010;van Oers and Mueller, 2010;Shaw and Øverli, 2012;Caramaschi et al, 2013;Carere and Maestripieri, 2013;Holtmann et al, 2016;Abbey-Lee et al, 2018a). Ropinirole, prescribed to treat restless leg syndrome and Parkinson's disease (Connolly and Lang, 2014), is a dopamine agonist at D2 and D3 dopamine receptors (Shill and Stacy, 2009). Importantly, research suggests that the monoamine systems are not fully independent, with many chemicals that can alter behavior having affinities for both serotonin and dopamine receptors (Bischoff et al, 1986;Lejeune and Millan, 1998;Lawler et al, 1999;Borroto-Escuela et al, 2010;Martínez-Clemente et al, 2012;de Bartolomeis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%